Effect of inspiratory muscle fatigue on exercise performance taking into account the fatigue-induced excess respiratory drive - Wüthrich, T. U.; Notter, D. A.; Spengler, C. M. (Experimental Physiology, 2013)
Inspiratory muscle fatigue (IMF) is suggested to compromise exercise performance, possibly via a respiratory muscle metaboreflex that impairs blood flow to working muscles, thereby accelerating the development of fatigue in these muscles. Cycling with IMF has also been associated with an excess ventilatory response, which could per se impair performance. Therefore, the present study investigated whether prior-induced IMF would affect subsequent cycling performance via increased quadriceps muscle fatigue alone and whether fatigue-induced excess ventilation would contribute to this impairment. Fourteen healthy male subjects (peak oxygen uptake, 57.0 ± 5.5 ml min-1 kg-1) cycled to exhaustion at 85% of their maximal work output with prior-induced IMF (PF-EX) and without prior-induced IMF (C-EX). Subjects then cycled twice for the duration of PF-EX but without prior IMF, once with spontaneous breathing (C-ISO) and once with breathing coached to match PF-EX ventilation (MATCH-ISO). Inspiratory muscle (Ptw) and quadriceps muscle contractility (Qtw) was assessed via magnetic nerve stimulation before and after exercise. The time to exhaustion in the PF-EX conditions was significantly reduced by 14% compared with C-EX. The reduction in Ptw and Qtw was greater after PF-EX (Ptw, 17.3 ± 9.7%; Qtw, 32.0 ± 10.8%) than after MATCH-ISO (Ptw, 10.8 ± 10.3%; Qtw, 23.3 ± 15.2%; P < 0.05), which may explain the increased perception of exertion and earlier task failure with prior-induced IMF. The augmented ventilatory drive had no effect on reductions in Ptw and Qtw after MATCH-ISO compared with C-ISO. Thus, prior-induced IMF reduces exercise performance, probably as a result of the increased quadriceps muscle fatigue and thus greater perception of exertion independent of the excess respiratory drive when cycling with fatigued inspiratory muscles.